AKTIVITAS MUKOLITIK FRAKSI METANOL DARI EKSTRAK ETANOL DAUN SIRIH MERAH (Piper crocotum Ruiz and Pav.) PADA MUKOSA USUS SAPI DAN KANDUNGAN KIMIANYA - Ririn Lispita Wulandari; Yulias Ninik Windriyati; Aqnes Budiarti (Universitas Wahid Hasyim Semarang, 2013)
ABSTRACT Red betel leaves (Piper crocotum Key words: red betel leaves, mucolitic, cow’s mucous Ruiz and Pav.) can cure many kinds of diseases, including cough. The aim of this research is to determine mucolitic activity of methanol fraction from ethanol extract of red betel leaves on cow’s intestine mucous in vitro and to identify its active compound group. Ethanol extract of red betel leaves was made by maceration method using ethanol 70%. Methanol fraction was made from ethanol extract by partitioned gradually using petroleum eter, ethyl acetate, and methanol. The obtained methanol fraction was made serial concentration started from 0.1%, 0.3%, 0.5%, 0.7%, 0.9% in 80% cow’s mucous. The mucolitic activity was tested using Viscometer Rion, and 0.1% acethylcystein as positive control. Identification the active compound using thin layer chromatography. The viscosity cow’s mucous analyzed statistically. Normality test using Shapiro Wilk, non parametric statistic test using Kruskal Wallis, and then continued using Mann Whitney Test with degree of trust of 95%.The result shows that methanol fraction has mucolitic activity whether at concentration 0.3% is equivalent to 0.1% acethylcystein. Methanol fraction contains saponin, flavonoid, and polyphenol.